A Nanotoxicological Approach to the Effects of Metformin and Sodium Metavanadate Co-encapsulated in Polycaprolactone Nanoparticles under the Biological Parameters of Zebrafish (Danio rerio) - , Tiago Queiroz da Mota Bittencourt; , Thamiris Pinheiros Santos; , Paulo Eduardo da Silva Bastos; , Marleyne José Afonso Accioly Lins Amorim; , Sâmara da Silva Gomes; , Yuri Mateus Lima de Albuquerque; , Pabyton Gonçalves Cadena (Archives of Current Research International, 2024)
The present study evaluated the sublethal and lethal effects, and heart rate of Danio rerio when exposed to antidiabetic drugs, metformin (M-10), and sodium metavanadate (V-10), their association (MV-10) and the polycaprolactone nanoparticles containing poloxamer 188 with (PPMV-1, PPMV-5, and PPMV-10) or without these antidiabetics (PP-10). Acute toxicity tests were carried out to evaluate these effects. Groups V-10, MV-10, PPMV-5, PPMV-10, and PP-10 had lethal and sublethal, such as effects as pericardial edema. Concerning the heart rate, the PPMV-1, PPMV-5, PPMV-10, and PP-10 groups had a reduction compared to the other groups, indicating toxicity of the constituents of the nanoparticles. PPMV-5, PPMV-10, and PP-10 groups had sublethal and lethal effects depending on the concentration. Antidiabetics were eliminated as a possible cause and the poloxamer 188 is non-toxic at the concentrations used. In the PP-10 group, there was a dynamic of sublethal and lethal effects like the PPMV-10 group. We conclude that the presence of PCL in the formulation of nanoparticles was harmful at the cardiovascular level in embryos and eleuthero-embryos of D. rerio, affecting their development and heart rate, regardless of their concentration. Because of the results obtained, we can conclude that the toxicological evaluation of a nanomaterial is important to anticipate problems in its veterinary application since such results show possible toxicity problems.